Detection of antimicrobial resistance genes in beta-lactamase- and carbapenemase-producing Klebsiella pneumoniae by patient surveillance cultures at an intensive care unit in Rio de Janeiro, Brazil - Claudia Flores; Célia Maria C. P. A. Romão; Kayo Bianco; Catia Chaia de Miranda; Angela Breves; Ana Paula S. Souza; Rosana Maria R. Santos; Bianca O. Fonseca; Ivano de Filippis; Maysa M. Clementino
ABSTRACT Introduction: The increasing incidence of multi-resistant microorganisms has been considered a public health problem. One of the routines included in hospital practice is the screening of colonized and/or infected patients. Objective: The aim of this study was to evaluate the genetic variability and clonal relationships of extended-spectrum beta-lactamase (ESBL)-producing K. pneumoniae, from surveillance cultures, at an intensive care unit, in Rio de Janeiro, Brazil. Material and methods: Seventy K. pneumoniae isolates were obtained from rectal swabs (March 2013 to March 2014). Antimicrobial susceptibility was assessed by VITEK 2 System. Resistant genes blaSHV, blaTEM, blaOXA-1, blaKPC, blaOXA-48, blaCTX-M-15, blaVIM, blaIMP and blaNDM were investigated by polymerase chain reaction (PCR); genetic diversity, by Enterobacterial Repetitive Intergenic Consensus-PCR (ERIC-PCR). Results: Strains showed high resistance rates to cefepime (94%), ceftazidime (96%), ertapenem (61%), imipenem (54%) meropenem (43%) and ciprofloxacin (69%). The most prevalent genes were blaSHV (69%), blaTEM (63%), blaOXA-1 (60%), blaKPC (57%), blaCTX-M-15 (47%), blaOXA-48 (16%). Genes blaVIM, blaIMP and blaNDM were not detected. Twenty nine profiles of resistance genes were observed, with 23% carrying at least five genes. A great genetic diversity (68 ERIC profiles) was also observed among the strains. Conclusion: Although no clonal relationship was observed within the isolates, this study revealed alarming data on the antimicrobial resistance deficiently monitored for preventive purposes in Brazil. Our data allow us to conclude that the inclusion of surveillance cultures in health facilities is a recommended strategy aiming particularly at preventing the spread of resistance genes in the hospital environment and, consequently, reducing morbidity and mortality.